Zspace founder to speak at Engineering open house - Armbruster, Shirley::::::::: (2013)
The Lyles College of Engineering's new 3D holographic technology for human computer interaction and its photogrammetry lab will be showcased in an open house today at Fresno State, from 3 to 4:30 p.m.